Genetic correlation estimates between direct and maternal genetic effects and estimates of the proportion of maternal permanent environmental variance to phenotypic variance for some important traits in Iranian fowls: A meta-analysis - Gholipour, Sedigheh; Ghavi Hossein-Zadeh , Navid; Darmani Kuhi , Hassan (Journal of Poultry Sciences and Avian Diseases, 2023)
Accurate estimation of genetic parameters is essential for setting selection plans in breeding programs. Over the past years, various studies reported the genetic parameters for different growth, reproduction, and egg quality traits in Iranian native fowls. These assessments were obtained using a variety of methods and from studies of different populations of native fowls, leading to significant variation in genetic parameter estimates. This study aimed to perform a meta-analysis based on a random-effects model to overcome the diversity of reported genetic parameters for economically important traits of Iranian native fowls. To summarize these results, a data set of information related to different growth, reproduction, and egg quality traits including 68 estimates of the proportion of maternal environmental variance to phenotypic variance (c2) and 38 genetic correlation estimates between direct and maternal genetic effects from articles published between 2007 and 2019 were used. Mean estimate of the proportion of maternal environmental variance to phenotypic variance for the studied traits showed that the highest estimate was related to body weight at hatch (0.273) and the lowest was for egg weight at the first day of laying (0.021). Estimation of proportion of maternal environmental variance to phenotypic variance was not significant for EN (P>0.05), but for other traits were significant (P<0.05). The genetic parameter estimates reported in this meta-analysis study are exploitable in breeding schemes when reliable estimates are not accessible for economically important traits in Iranian native fowls.